Anastrepha bistrigata Bezzi, 1919 and Anastrepha striata Schiner, 1868 (Diptera: Tephritidae) occurring sympatrically in Barreiras, Bahia, Brazil, and first record of both species in the state - Amaral, Tayron S.; Savaris, Marcoandre; Calado, Daniéla C.; Ribeiro, Ana E. L.; Zucchi, Roberto A. (Entomological Communications, 2023)
Anastrepha bistrigata Bezzi, 1919 and Anastrepha striata Schiner, 1868 (Diptera: Tephritidae) infest guava (Psidium guajava L.), but only A. striata is considered a serious pest in all countries where it occurs. Both species also exploit several other host plants. They are frequently collected in fruit fly surveys in Brazil, but it is unusual to collect them in the same locality. For this reason, we report the co-occurrence of A. bistrigata and A. striata in Barreiras, Bahia, Brazil, which is also the first record of both species in this state. Information on morphological identification, distribution in Brazil, hosts, and sympatric occurrences of these species is also provided.